PENGARUH WORK LIFE BALANCE, FLEXIBLE WORK ARRANGEMENTS, CAREER PLANNING TERHADAP KEPUASAN KERJA PADA BAZNAS BAZIS PROVINSI DKI JAKARTA - Rita Siti Fatimah; Ikvina Riska Baldina; Ghina Khofifah; Isna Nurjanah; Kurro Taqyun; Ratih Ayu Sekarini; Dhita Puspita Rini (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This research was conducted to determine and examine the influence of Work Life Balance, Flexible Work Arrangements, and Career Planning on the level of employee Job Satisfaction at Baznas Bazis DKI Jakarta Province. This study used a quantitative approach and survey method as data collection techniques. The study population consisted of 50 active employees of Baznas Bazis DKI Jakarta Province, all of whom were used as research samples. Data were obtained through distributing questionnaires using a Likert scale, while the data analysis technique used multiple linear regression analysis with the classical assumption test, t-test, F-test, and coefficient of determination test. The results of the study indicate that partially Work Life Balance and Flexible Work Arrangements have a positive and significant effect on employee Job Satisfaction. Meanwhile, Career Planning does not have a significant effect partially on Job Satisfaction. However, simultaneously the three independent variables have a significant effect on Job Satisfaction. The results of the coefficient of determination test indicate that Work Life Balance, Flexible Work Arrangements, and Career Planning are able to explain 52.1% of the variation in Job Satisfaction, while the rest is influenced by other factors outside the study. The results of this study are expected to be a consideration in making human resource management policies.